The concept and significance of forensic characteristics of the unlawful seizure of enterprise, institution or organisation property - S. V. Stetsenko (Bulletin of Kharkiv National University of Internal Affairs)
The unlawful seizure of property of an enterprise, institution or organisation is a fairly common criminal offence in the field of business activity. This criminal offence causes economic losses to both business entities and the state as a whole, reduces the level of economic security and, as a result, the level of investment, discredits the work of government agencies, undermines the authority of the state at the international level, etc. In order to overcome and prevent economic risks, it is necessary to develop a methodology for investigating a criminal offence under Article 206-2 of the Criminal Code of Ukraine.